Uterine scar rupture following medical termination of pregnancy in the first trimester: a case report - Yadav, Alka; Bhandari, Jeetendra; Pradhan, Binita; Shrestha, Reena (Journal of General Practice and Emergency Medicine of Nepal, 2024)
A twenty-five-year-old woman with G2P1L1A0 at 11WOG with no ANC visits presented to the Emergency department after taking Mifepristone and Misoprostol for unwanted pregnancy with complaints of generalized pain in the abdomen and PV bleeding. Her USG revealed previous ceasarean section uterine scar rupture. An emergency exploratory laparotomy was done. The fetus was floating in the pelvic cavity on the Right side of the uterus, and the whole thickness of the uterine scar rupture was noted and repaired.